An Evolutionary Agent-based simulation model for the industry life cycle - B. Cornelia Lehmann-Waffenschmidt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2008)
In contrast to the usual approach taken in the literature, in which an Industry Life Cycle (ILC) is reproduced by aggregate functions, the model of this paper generates a self-organizing ILC. A general evolutionary agent-based simulation model is developed that can be adapted for specific branches of industry. The results enable conclusions to be drawn for competition policy with regard to the workability of competition in the various phases of the ILC.
Keywords: L10; L11; O12; 330; Industry Life Cycle; Agent-Based Simulation Model; Evolutionary Economics; Lebenszyklus; Industrie; Agent-based Model; Simulation; Evolutionsökonomik; Theorie